Quality of life post laparoscopic repair of inguinal hernia: a prospective study at a tertiary care centre in Nepal - Bajagain, Santosh; Sah, Suresh Prasad; Khanal, Bhawani; Dwa, Manoranjan (International Surgery Journal, 2025)
Background: Post-operative quality of life, the most important outcome measure in inguinal hernia repair, has limited study in South Asian countries where laparoscopic inguinal hernia repair is relatively new. The study aimed to evaluate the outcome of laparoscopic hernia surgery in terms of Quality of life with a 6 months follow-up. Methods: 50 patients who underwent laparoscopic totally extra peritoneal (TEP) or laparoscopic trans-abdominal pre peritoneal (TAPP) inguinal hernia repair were prospectively evaluated till 6 months post-operation using the Carolinas Comfort Scale in this study after Institutional Review Committee’s approval and consent from patients. Results: Mean patient age was 49.68±16.69 years. 96% were males The overall mean operating time was 88.70±11.94 min (Range: 70 to 115 min). The mean length of hospital stay was 28.16±8.66 hours. At three weeks post-operation, the percentage of patients indicating no or mild but non-bothersome symptoms was 93% for sensation of mesh, 88% for pain, and 88% for movement limitation, which improved to 94% for sensation of mesh, 92% for pain and 94% for movement limitation at six months. Chronic pain, persistent for more than 3 months, was present in 10% patients. Conclusions: The quality of life during post-laparoscopic hernia repair was similar to other published literatures.